Modification of Mechanical Coffee Pulper Equipment - Willian Putra Marbun; Achwil Putra Munir; Lukman Adlin Harahap (Universitas Sumatera Utara, 2015)
Capacity constraints of Mechanical cofee skin peeler is one of the obstacles in increasing coffee production. To overcome this, we need a mechanical coffee skin peeler that has been modified. The study was conducted with the study of literature and make observations about the mechanical coffee skin peeler that has been designed Johanes Mikael Manulang, and then designed the coupling components that would be modified. The effective capacity of the tool was 206.57 kg/h or 1441.44 kg/day. The value of the effective capacity of the equipment was greater than the previous coffee skin peeler i.e 117.39 kg/h or 821.73 kg/day. Basic costs to be incurred was Rp. 73 953 /kg in year 1, Rp. 68.917 / kg in year 2, Rp. 67.241/kg in year 3, Rp. 66.404 /kg in the 4th year, and Rp. 65.903 /kg in the 5th year. This equipment would reach the break even point after peeling coffee at 9124.41 kg/year. Net present value of these equipment with 6% interest rate was Rp. 279,299,067.30 which means that the business is feasible. Internal rate of return was 7.21%. Keyword: modification, pulper equipment, skin